2018
DOI: 10.1111/trf.14997
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different standard red blood cell storage temperatures on human and canine RBC hemolysis and chromium survival

Abstract: BACKGROUND Storage temperature is a critical factor for maintaining red-blood cell (RBC) viability, especially during prolonged cold storage. The target range of 1 to 6°C was established decades ago and may no longer be optimal for current blood-banking practices. STUDY DESIGN AND METHODS Human and canine RBCs were collected under standard conditions and stored in precision-controlled refrigerators at 2°C, 4°C, or 6°C. RESULTS During 42-day storage, human and canine RBCs showed progressive increases in sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…In our study, less hemolysis was found at 0-6°C, with a minimum at 2.5°C (Fig. 3 a-c), which is in agreement with the results of (Blaine et al 2019), who found that storage at 2°C give better viability of human RBCs which they ascribed reduced RBC metabolism, such as slower pH drop due to slower formation of lactate. Furthermore, the FDA-approved storage temperature of human RBCs is at 1-6°C (FDA 2018).…”
Section: The Effect Of Temperaturesupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, less hemolysis was found at 0-6°C, with a minimum at 2.5°C (Fig. 3 a-c), which is in agreement with the results of (Blaine et al 2019), who found that storage at 2°C give better viability of human RBCs which they ascribed reduced RBC metabolism, such as slower pH drop due to slower formation of lactate. Furthermore, the FDA-approved storage temperature of human RBCs is at 1-6°C (FDA 2018).…”
Section: The Effect Of Temperaturesupporting
confidence: 92%
“…Similarly, high osmotic pressure could appear, e.g., in pre-salting and marinating steps which comprise salt solutions from om 3% up to saturation. Other factors which could be critical to RBCs would be the mechanical stress which appears, e.g., during transport and sorting of fish, as well as temperature fluctuations (Blaine et al 2019). Although the temperature is normally close to 0°C early in the process chain (Grahm et al 1992;Huss 1995), it can raise, e.g., in filleting and washing steps and in the handling of by-products (Kuhlin 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to previous studies, our study demonstrated an increase in lactate concentrations and pCO 2 during storage. 14 , 28 , 29 , 30 During storage, erythrocyte metabolic function is more dependent on anaerobic metabolism, which requires the conversion of intra‐cellular pyruvate to lactic acid. 28 , 31 During storage, the erythrocyte intracellular concentration of 2,3‐diphosphoglycerage (2,3‐DPG) decreases, which reduces RBC oxygen carrying capacity and promotes anaerobic metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In both human and veterinary medicine, storage of blood products can increase erythrocyte fragility, causing an increase in in vitro hemolysis and free Hgb concentrations. 15 , 29 , 36 , 37 , 38 An increase in red cell fragility and hemolysis can result in the release of cell‐free Hgb, which can contribute to multiple organ failure, 39 lung injury, 40 , 41 , 42 , 43 , 44 bacterial infections, 19 systemic and pulmonary hypertension, 40 kidney injury, and endothelial dysfunction. 21 Hemoglobin effectively scavenges nitric oxide, causing endothelial dysfunction, vasoconstriction, platelet aggregation, increased vascular permeability, and leukocyte adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…We next examined the influence of storage temperature on RBC viability using ex vivo human and canine RBCs as well as in vivo radiochromium-labeled RBC transfusions in canines [20]. The 1-6…”
Section: The Effects Of Temperature On Rbc Storage Lesionmentioning
confidence: 99%